Retensi Protein Lemak Ikan Gabus (Channa sp.) dengan Penambahan Arang Aktif dan Kitosan dengan Dosis Berbeda pada Pakan - Kalimansyah, Kalimansyah; Nurhayati, Nurhayati; Handayani, Lia; Almuqaramah, T.M Haja (Jurnal TILAPIA, 2025)
Lipid and protein retention are essential indicators for evaluating nutrient utilization efficiency in fish. These parameters reflect the organism's ability to absorb, store, and metabolize dietary lipids and proteins. Optimizing nutrient retention is closely related to feed quality, including the use of functional feed additives that enhance the nutritional and physiological performance of fish. Activated charcoal and chitosan are two promising feed additives known for their potential to improve feed efficiency. Activated charcoal acts as a porous adsorbent with a high surface area, enabling it to effectively bind and remove toxins and metabolic waste from the digestive tract. Meanwhile, chitosan—a derivative of chitin—possesses antimicrobial and immunostimulant properties and is capable of improving gut health, which supports better metabolic function and nutrient absorption. This study aimed to evaluate the effects of dietary supplementation with activated charcoal and chitosan on lipid and protein retention in striped snakehead (Channa striata) and to determine the optimal dosage combination. The experiment was conducted using a Completely Randomized Design (CRD) with six treatments and three replications. The treatments were as follows: A (control, no additive), B (2% activated charcoal), C (3% chitosan), D (1% activated charcoal + 3% chitosan), E (1.5% activated charcoal + 3% chitosan), and F (2% activated charcoal + 3% chitosan). The test fish were juvenile snakeheads with an average length of 3 ± 0.5 cm, stocked at a density of 20 fish per aquarium. Observed parameters included lipid retention, protein retention, weight and length gain, feed efficiency, and feed conversion ratio (FCR) over a 70-day rearing period. The results indicated that treatment D (1% activated charcoal + 3% chitosan) yielded the best performance in terms of protein retention (16.24%), weight gain (2.71 g), length gain (3.19 cm), feed efficiency (32.96%), and the lowest feed conversion ratio (3.04). In contrast, the highest lipid retention (3.33%) was observed in the control group (A).